2021
DOI: 10.1123/japa.2019-0484
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Perceptions of a Digital Intervention to Promote Physical Activity in Older Adults

Abstract: Purpose: This study explored participant views of a web-based physical activity intervention for older adults and examined how they resonate with the key principles that guided intervention development. Methods: Qualitative interviews were carried out with 52 older adults. A deductive qualitative analysis approach was taken, based around the intervention’s key principles. Results: Participants expressed mostly positive views of the intervention features, broadly confirming the appropriateness of the key princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…For example, adequate digital health literacy [10] and human support [11,12] are required to operate and potentially benefit from digital technologies. In general, co-creation and feedback from older users are required to develop appropriate digital technologies for healthy aging in this target population [13][14][15]. Furthermore, evaluation of cost-effectiveness [16] and user outcomes in the context of health promotion and disease prevention [17] is required to better understand if and how digital technologies work.…”
Section: Introductionmentioning
confidence: 99%
“…For example, adequate digital health literacy [10] and human support [11,12] are required to operate and potentially benefit from digital technologies. In general, co-creation and feedback from older users are required to develop appropriate digital technologies for healthy aging in this target population [13][14][15]. Furthermore, evaluation of cost-effectiveness [16] and user outcomes in the context of health promotion and disease prevention [17] is required to better understand if and how digital technologies work.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the domain of physical activity (PA) promotion have often used end-users as part of the process evaluation of interventions, which has informed the development and adaptation of later (versions of) interventions. Semi-structured interviews are frequently used after a period of using the intervention in order to gain further insights into the usability and feasibility ( Baretta, Perski & Steca, 2019 ; Degroote et al, 2020 ; Pollet et al, 2020 ). While this allows for user-input that can inform the development and adaptation of later (versions of) interventions, it does not involve end-users in the development process itself.…”
Section: Introductionmentioning
confidence: 99%
“…While this allows for user-input that can inform the development and adaptation of later (versions of) interventions, it does not involve end-users in the development process itself. However, there are other examples of studies that have made use of participatory design approaches, including think-aloud interviews ( Pollet et al, 2020 ; Poppe et al, 2017 ; Rowsell et al, 2015 ), prototype activities ( Van Hierden, Dietrich & Rundle-Thiele, 2021 ), individual and group (feedback) interviews ( Ehn et al, 2021 ; Van Hierden, Dietrich & Rundle-Thiele, 2021 ), focus groups ( Heffernan et al, 2016 ), informal guerilla testing ( Heffernan et al, 2016 ) and advisory Facebook groups ( Heffernan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“… 12 14 Computer-tailoring techniques even enable personalization at low cost 15 and simultaneously entail sustainable and scalable properties allowing widespread dissemination. 16 , 17 When looking at the effectiveness, there is growing evidence that blended PA interventions—a new delivery mode of linking face-to-face with digital components—show more promising results in older adults than the separated components. 18 20 A meta-analysis showed that, in the short term, digital behavior change interventions to promote PA and/or reduce sedentary behavior in older adults aged ≥ 50 years may lead to increases in PA levels and physical functioning as well as reductions in sedentary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The myriads of available websites and apps tend to focus on younger adults with higher levels of digital literacy. 17 Digital technologies aiming at older adults are required to be designed appropriately in order to be suitable for them. 22 , 34 Shaping DIs to promote PA to an older audience requires a prudent approach because barriers to uptake and use remain in older adults.…”
Section: Introductionmentioning
confidence: 99%